The book of joan ebook A novel. - Yuknavitch, Lidia (2017)
A New York Times Notable Book • BuzzFeed 50 Books We Can't Wait to Read this Year • New York Times Book Review Editor's Choice • National Bestseller "Brilliant and incendiary." — Jeff VanderMeer, New York Times Book Review "Stunning. . . . Yuknavitch understands that our collective narrative can either destroy or redeem us, and the outcome depends not just on who's telling it, but also on who's listening." — O, The Oprah Magazine "[A] searing fusion of literary fiction and reimagined history and science-fiction thriller and eco-fantasy." — NPR Books The bestselling author of The Small Backs of Children offers a vision of our near-extinction and a heroine—a reimagined Joan of Arc—poised to save a world ravaged by war, violence, and greed, and forever change history In the near future, world wars have transformed the earth into a battleground. Fleeing the unending violence and the planet's now-radioactive surface, humans have regrouped to a mysterious platform known as CIEL, hovering over their erstwhile home. The changed world has turned evolution on its head: the surviving humans have become sexless, hairless, pale-white creatures floating in isolation, inscribing stories upon their skin. Out of the ranks of the endless wars rises Jean de Men, a charismatic and bloodthirsty cult leader who turns CIEL into a quasi-corporate police state. A group of rebels unite to dismantle his iron rule—galvanized by the heroic song of Joan, a child-warrior who possesses a mysterious force that lives within her and communes with the earth. When de Men and his armies turn Joan into a martyr, the consequences are astonishing. And no one—not the rebels, Jean de Men, or even Joan herself—can foresee the way her story and unique gift will forge the destiny of an entire world for generations. A riveting tale of destruction and love found in the direst of places—even at the extreme end of post-human experience—Lidia Yuknavitch's The Book of Joan raises questions about what it means to be human, the fluidity of sex and gender, and the role of art as a means for survival.